Correlação entre IMC e parâmetros motores: uma análise em atletas masculinos de futevôlei - RODRIGUES, Gabriel Moutinho (2022)
This study seeks to clarify the physical abilities involved in footvolley and its influences. This work was carried out in Belém do Pará and aims to analyze the relationship between BMI and its influence on motor performance in amateur athletes of the sport. Cross-sectional and observational study, with a convenience sample of male amateur volleyball athletes in the city of Belém, in the state of Pará. minimum one (01) year of practice and age between 18 and 35 years (mean: 26.6 years / Standard deviation: ±4,14). All were evaluated equally through an anthropometric assessment that measured body mass (kg) and height (m) Application of vertical jump and agility plyometric tests (shuttlerun) Descriptive analysis was performed using Pearson's correlation, a value greater than 0 indicates a positive association, that is, as the value of a variable increases, the same happens with the value of the other variable. A value less than 0 indicates a negative association, that is, as the value of one variable increases, the value of the other decreases. A correlation of (ρ) = - 0, was found. 80 for BMI and Vertical Jump, being inversely proportional variables and (ρ) = 0.85 for BMI and Shuttlerun, as directly proportional variables, in addition to evidencing a strong relationship between them. Therefore, it was possible to observe that there is a direct influence of the BMI on the motor performance of the evaluated athletes. Therefore, athletes with higher BMI have a lower jumping power.